(untitled) (Journal of the College of Basic Education, 2022)
To delve into the subject of the Arab tribes in terms of affiliation, places of residence and their role in eventsDiameter. Which witnessed political developments and local conflicts between the tribal forces themselves or between them and neighboring forceson the side of difficulty; For factors related to the difficulty of defining the concept of the nature of these tribes and the direction of their orientation and whatIt is the nature of its approach in managing its internal affairs and dealings in its external relations. inAt a time when those forces were not convinced of the need to abandon their own disputes and go to establish institutionsfor a country you intend to establish; Because of the unstable conditions experienced by Qatar and the Arab Gulf region earlyModern times and this continued in the nineteenth century.